Inhibitory Efficacy of Croton gibsonianus Nimm. Grah (Euphorbiaceae) Against Oral Isolates of Streptococcus mutans - N, Mallikarjun (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTThe present research was undertaken to investigate the anticariogenic activity of methanol extract of Croton gibsonianus Nimm. Grah (Euphorbiaceae) leaves. The shade dried leaves were powdered and extracted with methanol. The inhibitory efficacy of methanol extract was tested against 24 oral isolates of Streptococcus mutans by Agar well diffusion method. The extract caused a dose dependent inhibition of cariogenic isolates. Preliminary phytochemical analysis showed the presence of saponins, glycosides, tannins and terpenoids. The inhibitory efficacy of extract against cariogenic isolates could be due to the presence of these metabolites. In suitable form, the plant could be used to treat dental caries. Further study is needed to identify the bioactive components and their efficacy against cariogenic bacteria.